Oh, rats! - Seidler, Tor (New York : Atheneum Books for Young Readers, 2019)
"A New Jersey squirrel named Phoenix teams up with a pack of rats in New York City to save their riverside home from being demolished and turned into a high-rise"--
"A Caitlyn Dlouhy Book."